The structural class action as a way to remedy the symbolic normativity of environmental education (Research, Society and Development, 2021)
The lack of environmental awareness and critical education is a worldwide challenge. The present article aims to study the structural process of public interest as a way to implement an effective environmental education, before the power and duty of State and social performance of the environment. For the approach, the hypothetical-deductive method will be used, the qualitative exploratory research based on bibliographic and documental survey. It is verified as a result that the structural process of public interest can be a capable instrument for the effectiveness of environmental education, by urging the Public Power, through structuring measures, to insert it as a mandatory subject in Brazilian basic education.